KIKUCHUI- FUJIMOTO DISEASE: Kikuchui- Fujimoto Disease - Sabir, Sohail; uddin, Hafeez; Khan, Tariq (Pakistan Armed Forces Medical Journal, 2009)
INTRODUCTIONKikuchi's disease first described in 1972 by Kikuchi and Fujimoto et al usually manifests as a localized cervical adenopathy, primarily in the posterior neck of young women [1]. Its course is benign, but can be misdiagnosed as lymphoma, both clinically and pathologically [2].